A glitter of gold - Johnson, Liz, 1981- (Johnson, Liz. Georgia Coast romance, 2019)
"When pirate wreck tour guide Anne Norris finds evidence of an undiscovered shipwreck, she seeks the help of museum director Carter Hale to uncover the truth and treasure that could save her business. But can she trust him with her secrets and her heart?"--